Study on Mechanical and Acoustic Emission Characteristics of the Influence of Rock Bridge Length on Rock Failure - Jianchao Wang; Yan Zhang; Changan Qin; Yaohui Gao; Zhaofeng Wang; Guofeng Zhang (Lithosphere, 2022)
AbstractRock bridge of jointed rock plays a key role in its instability failure and has great influence on underground engineering. In this paper, the direct shear tests of jointed rocks with different rock bridge lengths are carried out, and the mechanical properties, acoustic emission (AE) characteristics, and fracture mechanism during the failure of rock bridge are studied. The results show that the shear strength increases with the increase of normal stress. When the rock bridge is long, cohesion c plays a leading role to control the failure of jointed rock; on the contrary, the internal friction angle φ plays a leading role. AE count rate, cumulative AE counts, and peak AE energy rate increase with the increase of rock bridge length. With the increase of rock bridge length, peak AE energy rate and AE count rate occur earlier. Considering the influence of rock bridge length, the fracture criterion and crack growth angle of shear fracture are derived based on linear elastic fracture mechanics. The theoretically calculated result is consistent with the experimental result. The research in this paper can provide relevant theoretical basis and useful reference for the instability and failure analysis of jointed rock.